Efficient visible light photocatalytic degradation of 17α-ethinyl estradiol by a multifunctional Ag–AgCl/ZnFe2O4 magnetic nanocomposite. Issue 39 (4th April 2016) - Upreti, Akhanda Raj; Li, Yi; Khadgi, Nirina; Naraginti, Saraschandra; Zhang, Chi
Abstract : Magnetic separability and photocatalytic enhancement by plasmonic property of Ag–AgCl/ZnFe2 O4 nanocomposite makes it practicable in both environmental and economic terms. Abstract : The visible light active magnetic photocatalyst ZnFe2 O4 was prepared via a facile hydrothermal and deposition–precipitation method using UV irradiation for photoreduction of Ag over AgCl for various durations. The Ag–AgCl/ZnFe2 O4 nanocomposite (NC) showed efficient photocatalytic activity for the degradation of 17α-ethinylestradiol (EE2), a recalcitrant endocrine disrupting compound. The pseudo rate constant ( k ′) of as-synthesized Ag–AgCl/ZnFe2 O4 NC photo-reduced for 60 minutes was higher by a factor of 18.3 times compared to the ZnFe2 O4 alone. In this Ag–AgCl/ZnFe2 O4 NC, plasmon-excited Ag nanoparticles (NP) served as electron-transfer media, while ZnFe2 O4 also participated in the charge transfer, besides serving as a support for Ag–AgCl. The electron transfer from ZnFe2 O4 to Ag to AgCl in the Ag–AgCl/ZnFe2 O4 NC enhances the interfacial charge transfer, and also contributes to the stability of the composite. Further, the composite can be magnetically separated for reuse. Hence, Ag–AgCl/ZnFe2 O4 has a good potential in the field of environmental applications.